Understanding (meaning assignment to) assessment in teachers, teacher-trainers and teacher-trainees at UMCE (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
The research aims to understand how teachers, teacher-trainers and teacher-trainees assign meaning to the assessment process and how this process of meaning generates a vision of the world, perspectives, and a basis of support for teachers. Using a qualitative interpretative methodology based on narrative intelligibility and using a case study and in-depth interviews, this research reveals subjectivities around the role of assessment in the space of the university.